Occurrence of antibodies against Leptospira spp. in donkeys of São Paulo state - Maria do Carmo Custódio de Souza Hunold Lara; Eliana Monteforte Cassaro Villalobos; Elenice Maria Sequetin Cunha; José Victor de Oliveira; Vanessa Castro; Alessandra Figueiredo de Castro Nassar; Lília Márcia Paulin Silva; Liria Hiromi Okuda; Adriana Hellmeister de Campos Nogueira Romaldini; Mariana Sequetin Cunha; Eduardo Carvalho Marques; Enio Mori (Arquivos do Instituto Biológico)
ABSTRACT: Among the diseases that affect equines, bacterial diseases play an important role from a health and economic point of view, especially leptospirosis and brucellosis. The study aimed to provide information on the occurrence of anti-Leptospira spp. and anti-Brucella abortus antibodies in donkeys of São Paulo state. We found a frequency of 62.4% (53/85) antibodies against Leptospira spp. The donkeys were not seropositive for Brucella spp.